Chelidamic acid derivatives: Precursors to functionalized pyridyl cryptands & functionalized metal ligands. (13th August 2021) - Gibson, Harry W.; Price, Terry L.; Pederson, Adam M.-P.; Niu, Zhenbin; Nellipalli, Pothanagandhi
Abstract: Pyridyl cryptands, such as 12 –16 formed from pyridine-2, 6-dicarbonyl chloride (4 ) and crown ether diols 7 –11, have been demonstrated to be excellent hosts for viologens ( N, N′ -dialkyl-4, 4′-bipyridinium salts, 2 ) with K a values of ∼10 4 to 10 6 M −1 and thus are considered to be ideal building blocks for supramolecular systems. However, in order to incorporate these host motifs into useful starting materials, functionalization is required; in this article we describe syntheses of 23 new chelidamic acid (2, 6-dicarboxy-4-hydroxypyridine, 5 ) derivatives that can be used to prepare functional pyridyl cryptands and functional metal ligands. The preparation and characterization of three new functionalized pyridyl cryptands are also included. Graphical abstract: New functional building blocks for pyridyl cryptand hosts for supramolecular chemistry and ligands for active metal complexes. Image 1